Analisis Gaya Kepemimpinan Kepala Desa dalam Mendukung Pengelolaan Badan Usaha Milik Desa (Studi Kasus BUMDesa Long Jinawi Desa Galengdowo Kecamatan Wonosalam Kabupaten Jombang) - Hidayati, Umi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
This study aims to explain the leadership style of the Galengdowo village head, Wonosalam District, Jombang Regency in carrying out its role in the management of Village Owned Enterprises (BUMDesa), which is focused on three aspects, namely, providing advice to operational implementers in implementing the management of BUMDes in Galengdowo Village, providing advice and opinion on issues that are considered important for the management of BUMDes in Galengdowo Village, and controlling the implementation of BUMDes management activities in Galengdowo Village. The research method uses a qualitative approach, with the type of case study research. Data collection techniques are interviews, observation and documentation. The data analysis technique used the Miles and Huberman interactive model analysis. From the results of the study, it is known that the leadership style of the Galengdowo Village Head in carrying out his role in the three aspects above uses a participatory leadership style, this is proven in every role that always involves all elements of the community to discuss and exchange opinions to find solutions to problems that arise in the management of BUMDes. Long Jinawi. This is important when creative thinking is needed to solve complex problems or make decisions that will impact the overall management of the BUMDes.